Upaya Guru Dalam Mengembangakan Kognitif Dan Kreativitas Anak Usia 4-5 Tahun Melalui Permainan Puzzle Di TK Negeri 25 Rabangodu Utara Kota Bima - Nurillah Nurillah; Ihlas Ihlas; Khairuddin Khairuddin; Lukman Lukman (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2023)
Research that describes how much effort teachers put into developing the cognitive and creativity of children aged 4-5 years through puzzle games. The aim of this research is to find out how teachers use it and the obstacles they face in teaching children to play puzzles to develop the cognitive and creativity of children aged 4-5 years at Kindergarten 25 Rabangodu Utara, Bima City. The research method used in this research is a descriptive qualitative method. Specifically, qualitative research methods involve data collection techniques through in-depth interviews and participant observation. Apart from that, qualitative data analysis using a descriptive approach is used as a data analysis technique. The results of the research conducted by the author show that puzzle games have a very good impact on the cognitive development and creativity of children at Al Mahasin Bima Kindergarten. Through puzzle games, children can learn about early literacy, differentiate between objects, practice concentration, learn to be patient, solve problems and stimulate children to produce new works that are useful for themselves. The obstacles faced by teachers in teaching children to play puzzles are triggered by two factors, namely internal factors, including: children find it difficult to focus, are lazy, like to disturb their friends and children cannot yet be independent. Where he doesn't want to be left by his parents until it's time to get home from school. Meanwhile, the external factors are parents, schools (teachers), and the community environment.